RESPONS PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) YANG DIBERI BEBERAPA DOSIS PUPUK TRICHO KOMPOS KOTORAN AYAM - Hendri Irawan; Nurmayulis .; Dewi Hastuti (Jurnal Agroekoteknologi, 2018)
The research was aimed to know Growth and Yield Respons of Onion (Allium ascalonicum L.)) to Given Some Dose of Fertilizer on Tricho Compost Chicken Manure. This research was conducted in the village of Cidahu District of Banjarsari, Lebak, from February until April 2017. The research used Rondomized Completely Block Design, which was arranged as factorial with one factor. The factor was dose of tricho compost chicken manure  with six lavels   0, 5, 10, 15, 20 25 tonnes ha-1.  Thus, there are six treatments and each treatment was replicated four times as a group, so there are 24 experimental units. The results showed that various dose of tricho compost with 15 tonnes ha-1 give an significant effect on the number of bulb. The used of tricho compost did not give significant effect in plant’s height, number of leaves, plant’s weight, and dry plant’s weigth.                                                                                  Keywords: Fertilization, Onion, Trichoderma sp.